2008
DOI: 10.1111/j.1365-2486.2008.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant diversity positively affects short‐term soil carbon storage in experimental grasslands

Abstract: Increasing atmospheric CO2 concentration and related climate change have stimulated much interest in the potential of soils to sequester carbon. In 'The Jena Experiment', a managed grassland experiment on a former agricultural field, we investigated the link between plant diversity and soil carbon storage. The biodiversity gradient ranged from one to 60 species belonging to four functional groups. Stratified soil samples were taken to 30 cm depth from 86 plots in 2002, 2004 and 2006, and organic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
227
7
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(252 citation statements)
references
References 53 publications
16
227
7
2
Order By: Relevance
“…In contrast, the positive plant diversity effect on soil carbon storage (Table 1), root biomass 39 and soil microbial biomass 40 was also found for deeper soil layers in The Jena Experiment. Despite the consistency of the plant diversity effect, it may be strongest in the topsoil and decrease with soil depth 25,39 , which may be due to the fact that root carbon inputs 24,39 and microbial activity 41 decrease with soil depth. Therefore, the mechanism proposed for the topsoil is very likely to also be relevant for deeper soil layers, but the decreased biological activity at the deeper soil layers has to be taken into account.…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, the positive plant diversity effect on soil carbon storage (Table 1), root biomass 39 and soil microbial biomass 40 was also found for deeper soil layers in The Jena Experiment. Despite the consistency of the plant diversity effect, it may be strongest in the topsoil and decrease with soil depth 25,39 , which may be due to the fact that root carbon inputs 24,39 and microbial activity 41 decrease with soil depth. Therefore, the mechanism proposed for the topsoil is very likely to also be relevant for deeper soil layers, but the decreased biological activity at the deeper soil layers has to be taken into account.…”
mentioning
confidence: 92%
“…Alternatively or in parallel, higher amounts of plant residue inputs could enhance carbon storage through increased microbial necromass accumulation over time 23 . Therefore, although soil carbon storage increased with plant diversity in a number of long-term grassland experiments 24,25 , the underlying mechanisms are yet to be understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tree leaves, tree roots, and the herbaceous vegetation from the tree row have different C : N ratios, lignin, and cellulose contents than the crop residues. Recent studies showed that plant diversity had a positive impact on SOC storage (Lange et al, 2015;Steinbeiss et al, 2008). One of the hypotheses proposed by the authors is that diverse plant communities result in more active, more abundant, and more diverse microbial communities, increasing microbial products that can potentially be stabilized.…”
Section: Higher Oc Inputs or A Different Quality Of Oc?mentioning
confidence: 99%
“…Root-derived C is thought to be the main and the most stable source of SOC in grasslands, and belowground litter and productivity, and C stocks are more important for C sequestration (Steinbeiss et al, 2008a(Steinbeiss et al, , 2008b. The SOC stock belowground at a soil depth of 15 cm was 3619 g C m −2 in the GfGP grassland, and was considerably greater than that in the corresponding cropland (2902 g C m −2 ) but less than in the natural grassland (4779 g C m −2 ; Tables 1 and 2), which highlights the benefits of the GfGP for grassland C sequestration.…”
Section: Effects Of the Gfgp On C Stocksmentioning
confidence: 99%